AN ECONOMIC ANALYSIS OF THE ROLE OF RURAL WOMEN IN IMPROVING FARM INCOME AND LIVING STANDARDS. - Abed , M. N.; Ahmad, A. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to determine the contribution of women in diversifying sources of farm income, thereby improving the standard of living of the rural family, through their work in various primary and secondary agricultural production activities. Rural women in Iraq constitute a large part of the family’s farm work. In addition to her paid work on other farms. Despite the significant role of rural women’s contribution to production processes. However, the percentage of their participation in some agricultural operations is less than that of men due to their limited control over production and marketing decisions. This is reflected negatively in their ability to generate income. The research used cross-sectional data for a random sample that included (384) women from separate rural areas in Baghdad governorate to determine the effect of the working hours of women and men in addition to the number of animals owned by women on the size of the total farm income through the use of the OLS model, the ordinary least squares method with the double logarithmic formula. The results showed that increasing the number of working hours for women positively affects the increase in farm income. Moreover, the size of the parameters of women’s work in animal production activity (0.16) and industry (0.15) were more influential than men’s work (0.08(. As for the plant production side (0.26), its effect was less than that of men due to the existence of some activities that are specific to women rather than to men. Therefore, the research recommends the need for programs related to developing the skills of rural women in all agricultural activities, providing health and educational care for women, and empowering women financially and technically to increase their contribution to income generation and improve the standard of living for the family.